En defensa del textualismo contractual: una lección del Common Law - Benatti, Francesca (2024)
The text examines the two methods of interpretation used in the American Common Law: textualism and contextualism. After looking at the parties’ preference for textualism, it highlights the reasons why it appears to be the most effective method. This method is more respectful of their wishes and is able to interpret the needs of the business world more effectively. The practical reality shows how the same parties can decide how to make the context relevant.